ANALISA GUGUS FUNGSI PADA NANOPARTIKEL MAGNESIUM FERRITE (MgFe2O4) YANG DIENKAPSULASI DENGAN POLYETHYLENE GLYCOL (PEG-4000) DAN SILIKA - Deska Lismawenning Puspitarum (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Magnesium Ferrite Magnesium (MgFe2O4) magnetic nanoparticles have been successfully carried out by varying the concentrations of PEG-4000 and silica as encapsulation materials using coprecipitation methods. The X-ray Diffraction (XRD) analysis showed that new phases appeared in MgFe2O4 after PEG-4000 encapsulation, ie Î±-Fe2O3 having a paramagnetic rhombohedral and Î³-FeO (OH) structure. The particle size of MgFe2O4 before encapsulation was 10.5 nm, after encapsulation with PEG-4000 became 5.2 nm and encapsulation with silica became 18.8 nm. In encapsulation with silica, the peak of the new diffraction field 222 which is a crystal appears. The result of Fourier Transform Infra-Red (FTIR) analysis showed that in MgFe2O4 coated with PEG-4000, there was a shifting in the wave number 2885.5 cm-1 to 2924.1 cm-1 in CH bond which was the bond of PEG- 4000 and a shifting in the wave number 316.3 cm-1 to 300.9 cm-1 on the metal oxide bond (MO) which is a uniform pattern of MgFe2O4. The presence of silica which has coated the magnetic material is shown in the 455.2 cm-1 number of Si-O-Si (bending) group.